2017
DOI: 10.1128/aem.00306-17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stability and Evolution of thesigBAllele, Used for Listeria Sensu Stricto Subtyping and Phylogenetic Inference

Abstract: Sequencing of single genes remains an important tool that allows the rapid classification of bacteria. Sequencing of a portion of , which encodes a stress-responsive alternative sigma factor, has emerged as a commonly used molecular tool for the initial characterization of diverse isolates. In this study, evolutionary approaches were used to assess the validity of allelic typing for For a data set of 4,280 isolates, allelic typing showed a Simpson's index of diversity of 0.96. Analyses of 164 allelic types (AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…In addition, sampling sites representing drains showed repeat positives in three operations, with three drain-related sites showing repeat positives in packinghouse A. Whereas all isolates were characterized by sigB allelic typing, the data are consistent with findings from previous studies (1,5,16) that sigB sequencing alone has limited discriminatory power and is typically insufficient for establishment of persistent contamination, as supported by the fact that LM with sigB AT57 was found in all six operations that had LM positives. However, for two sites ("square drain 1" in packinghouse A and "rot bin under rollers" in packinghouse C; see Table 3), isolates with identical sigB ATs were obtained on three separate sampling dates; these sites had high priority for follow-up, including follow-up higher resolution subtyping.…”
Section: Prevalence Of L Monocytogenes and Othersupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, sampling sites representing drains showed repeat positives in three operations, with three drain-related sites showing repeat positives in packinghouse A. Whereas all isolates were characterized by sigB allelic typing, the data are consistent with findings from previous studies (1,5,16) that sigB sequencing alone has limited discriminatory power and is typically insufficient for establishment of persistent contamination, as supported by the fact that LM with sigB AT57 was found in all six operations that had LM positives. However, for two sites ("square drain 1" in packinghouse A and "rot bin under rollers" in packinghouse C; see Table 3), isolates with identical sigB ATs were obtained on three separate sampling dates; these sites had high priority for follow-up, including follow-up higher resolution subtyping.…”
Section: Prevalence Of L Monocytogenes and Othersupporting
confidence: 88%
“…The sequences were then trimmed for analysis of the 660-bp internal fragment to determine the sigB allelic type (AT) for each isolate. The sigB gene was used for initial subtyping and characterization due to its genetic stability and accuracy in species and lineage classifications, as previously detailed (16). Sequences were edited and assembled using Sequencher sequence analysis software (version 5.4.6, Gene Codes Corporation, Ann Arbor, MI) and were analyzed using MEGA7 (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reported that two strains, 76P1 (Table 3) and 1E1 (sigB AT 37; derived from the skin of beef cattle), possessed nonsense mutations in the sigB gene (6). According to genetic analysis of the sigB allele, this sequence was found to be relatively conserved in L. monocytogenes (14). We confirmed that only two strains, FSL J1-0086 (AT 103, isolate source: human sporadic listeriosis) and Cornell University (Ithaca, NY, USA) (14,15).…”
mentioning
confidence: 99%
“…According to genetic analysis of the sigB allele, this sequence was found to be relatively conserved in L. monocytogenes (14). We confirmed that only two strains, FSL J1-0086 (AT 103, isolate source: human sporadic listeriosis) and Cornell University (Ithaca, NY, USA) (14,15). In addition to these nonsense mutation-containing types of sigB (ATs 36, 37, 39-41, and 43), a new type of sigB (ATs 38 and 42) was identified that is not currently registered in either of the databases at the Pasteur Institute or Cornell University.…”
mentioning
confidence: 99%